2022
DOI: 10.3390/healthcare10122573
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress and the Resilience of University Students during the First Wave of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic had an impact on everyone’s daily lives with short-term or long-term consequences. Among the affected population, university students were studied by researchers specifically due to the total change to their educational way of learning and the courses they attended. The present study aimed to assess the psychological difficulties experienced by the university students of Greece during the first wave of the outbreak. Methods: 288 university nursing students completed an electronic question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
3
14
0
1
Order By: Relevance
“…3%, for dentistry: 26.3% and for nursing 13.5%) and depression (for the total sample: 18%, for dentistry: 20% and for nursing 15.9%). These rates are higher than in other studies in Greek nursing students during the first wave of Covid-19 pandemic [4]and frontline nurses in referral hospitals for Covid-19 [47]. Itʹs also noteworthy to observe that working nurses experience anxiety, while nursing students experience depression at a higher rate.…”
Section: Overall Levels Of Stress Anxiety and Depression Among Dental...mentioning
confidence: 59%
See 4 more Smart Citations
“…3%, for dentistry: 26.3% and for nursing 13.5%) and depression (for the total sample: 18%, for dentistry: 20% and for nursing 15.9%). These rates are higher than in other studies in Greek nursing students during the first wave of Covid-19 pandemic [4]and frontline nurses in referral hospitals for Covid-19 [47]. Itʹs also noteworthy to observe that working nurses experience anxiety, while nursing students experience depression at a higher rate.…”
Section: Overall Levels Of Stress Anxiety and Depression Among Dental...mentioning
confidence: 59%
“…Moderate to high degrees of resilience were found in the Labrague (2021) [72] study, which lessened the detrimental effects of COVID-associated stress on psychological well-being and life satisfaction. In a similar vein, Dafogianni et al (2022) [4] found that stress, anxiety, and depression were significantly negatively connected with resilience, life orientation, and active/positive coping, and positively correlated with negative affect score. In our study, stress and anxiety were associated with lower resilience levels.…”
Section: Resilience Level Of Both Nursing and Dental Studentsmentioning
confidence: 78%
See 3 more Smart Citations